Improved methods to prevent railway embankment failure and subgrade degradation: a review - Roshan, Mohammad Jawed; A. Rashid, Ahmad Safuan; Abdul Wahab, Norshakila; Tamassoki, Sakina; Jusoh, Siti Norafida; Hezmi, Muhammad Azril; Nik Daud, Nik Norsyahariati; Mohd Apandi, Nazirah; Azmi, Mastura (Elsevier, 2022)
Railway transportation is one of the most advantageous modes of transportation because of its high capacity, which obviates the increasing demand for conveying passengers and cargo. However, high initial costs and ongoing maintenance costs (partially resulting from the degradation of the subgrade and embankments) are drawbacks. Besides, railway subgrade soil experiences a high impact load and alternate drying-wetting and freeze-thawing cycles. In order to counter these problems, various kinds of soil improvement have been employed to improve the engineering properties of soils and minimise embankment and subgrade degradation. Chemical, mechanical, and geosynthetic techniques are currently being used to improve railway embankments. Some methods, such as columnar systems and deep mixing, fortify embankment foundations or subsoil, while others (e.g. chemical binders) can be used as mixed material to stabilise embankments and subgrade soil to a shallow depth. Hence, this review paper first discusses the correlation between railway track elements, failures, and the degradation of embankments in railway networks, and then compares the soil stabilisation techniques from multiple aspects.